Análisis de abandono y pérdida de valor funcional en el edificio del ex Consejo Provincial de Chimborazo y propuesta arquitectónica - Altamirano Muñoz, Edgar Francisco (2021)
The origin of modern architecture takes place in the west, just as in the context of the industrial revolution when avant-garde environments have been perceived and constantly evidence of societal change. As a perception of social conditions were; all these actions could be said to date at the beginning of the 20th century, but it was just until the middle of the same century that countries in Latin America assessed and decided to adopt this trend that marks an important moment of change in terms of technological development as well as formal and functional conceptions and perception of spatial occupation form—linked to the quality of life and habitability of users. Ecuador has received through its main cities this influence since the 1930s, and it has become much more notorious with the highly valued and substantial presence of essential architects, engineers, and artists, from Europe and Latin American. In subsequent decades the country incorporates the valuable contribution of significant architecture and its great importance to the development of cities in growth. The hands made this of those professionals who completed their professional training in the country. In this period, significant works were built whose historical recognition is transcendental in the modern image of a city. This research work reveals the causes of the current situation of many modern works in the country, but primarily studies the current conditions of a building named Ex-provincial Council, by Arq. Oswaldo Muñoz Mariño, located on Diez de Agosto St. and Spain St. in Riobamba, by the act of trying to recover the space, through an architectural proposal to integrate the work activities into the context of a historic center, even though these works marked the constructive technological development, as well as the search for of their own values in the immediate environment where they were implanted, it is actually evident the little interest from leading authorities to keep this building in a good way and give the value that it deserves.